Wealth creators or inheritors? Unpacking the gender wealth gap from bottom to top and young to old - Charlotte Bartels; Eva Sierminska; Carsten Schröder (Deutsches Institut für Wirtschaftsforschung (DIW), 2024)
There is growing interest in understanding how gender influences the accumulation of wealth. While prior studies focused on labor-related determinants, our research focuses on inheritances and gifts. Using unique survey data that oversamples the top 1% of wealth holders in Germany, we show that the gender wealth gap is small for individuals up to age 40, then widens, and declines for those past retirement age. Transfer amounts and their timing are important drivers of these differences: men tend to inherit larger sums than women during their working life. Women often outlive their male partners, thus receiving larger inheritances at older ages.
Keywords: D31; D63; J16; 330; Wealth Accumulation; Wealth Inequality; Gender Wealth Gap; Inheritances; Gender Economics